2004
DOI: 10.1097/01.sap.0000131275.62449.c8
|View full text |Cite
|
Sign up to set email alerts
|

Local Complications After Cosmetic Breast Implant Surgery in Finland

Abstract: Concerns regarding potential health effects of silicone breast implants have recently shifted from long-term illnesses to postoperative local complications. In this study, occurrence of local complications and treatment procedures were evaluated in a population of 685 Finnish women who received cosmetic silicone breast implants between 1968 and 2002. Patient records were abstracted, and additional information was gathered using a structured questionnaire that was mailed to 470 of the women in the cohort. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 22 publications
3
36
1
5
Order By: Relevance
“…Similar to the findings of this study, other reports have described the protective effect of submuscular placement with regard to the development of capsular contracture [8][9][10]23 and inframammary incision sites. 9,24,25 Regarding device size, Henriksen et al found that implants with volumes greater than 350 cc significantly increased the risks of complications requiring secondary surgical procedures.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the findings of this study, other reports have described the protective effect of submuscular placement with regard to the development of capsular contracture [8][9][10]23 and inframammary incision sites. 9,24,25 Regarding device size, Henriksen et al found that implants with volumes greater than 350 cc significantly increased the risks of complications requiring secondary surgical procedures.…”
Section: Discussionsupporting
confidence: 92%
“…The cohesive gel series were published between 2001 and 2006 (1,(16)(17)(18)(19)(20)(21)(22). Sample sizes ranged from n=14 to n=823.…”
Section: Cohesive Gel Series Resultsmentioning
confidence: 99%
“…Other different studies 8,13 showed patients and observer satisfaction with breast augmentation was over 90%. Results were similar with our study.…”
Section: Fig-3: E-h Operative Picture Of Subglandular Implant Placemmentioning
confidence: 99%